Entomological characterization of aedes mosquitoes and arbovirus detection in Ibagué, a Colombian city with co‑circulation of zika, dengue and chikungunya viruses - Carrasquilla, María Cristina (2021)
Fil: Carrasquilla, María Cristina. Universidad de los Andes; Colombia.